Big world for little people - Abad, Heidi Emily Eusebio; Bauza, Jamie (Quezon City LG & M, 2014)
"Imagine what it's like to see the world from just a few feet off the ground. You'll be surprised at how different it looks. Discover hidden corners and strange views of common objects in this book."
Keywords: Children's poetry, English; Philippine poetry (English)